Competitiveness of the Baltic States in International High-Technology Goods Trade - Falkowski, Krzysztof (Comparative Economic Research. Central and Eastern Europe, 2018)
The aim of the article is to assess the international competitiveness of the Baltic States (Estonia, Latvia, Lithuania) in high-technology goods trade. To this end, Balassa’s method of analysing revealed comparative advantages (RCA) was applied. An in-depth analysis of the dynamics of RCAs in the Baltic States’ exports between 1997 and 2014 has shown that their international competitiveness in this regard is relatively low, the direct consequence of which is the growing negative trade balance in high-technology goods. Also, during the analysed period Lithuania possessed no RCAs in trading high-technology goods, while the number of advantages for Estonia and Latvia was relatively small. Still, among the three Baltic States, Estonia was found to be most competitive in this regard, although in Latvia some progress was observed. In contrast, Lithuania not only had the lowest values of RCA, but also it did not record any improvement in the analysed period.